Value of three‐dimensional speckle‐tracking imaging in detecting left ventricular systolic function in patients with dilated cardiomyopathy - He, Jionghong (Echocardiography, 2019)
OBJECTIVE: To explore the value of three‐dimensional speckle‐tracking imaging (3DSTI) in detecting left ventricular systolic function in patients with dilated cardiomyopathy (DCM). METHODS: Totally 31 DCM patients were enrolled in this study. Left ventricular end‐systolic volume (LVESV), left ventricular end‐diastolic volume (LVEDV), and left ventricular ejection fraction (LVEF) were measured using the 3DSTI, two‐dimensional echocardiography (2DE), and magnetic resonance imaging (MRI). Left ventricular end‐diastolic mass (EDmass) and left ventricular end‐diastolic mass index (LVEDmass I) were also detected by 3DSTI and MRI. The differences in these measurements were analyzed and compared. RESULTS: The values of LVESV, LVEDV, and LVEF showed significantly positive correlations among 2DE group, 3DSTI group, and MRI group. The LVEF value showed significant difference among these three groups [(33.3 ± 11.1)%, (30.3 ± 10.6)%, and (26.2 ± 10.7)%; P = 0.04], whereas LVEDV and LVESV values were not significantly different (P > 0.05; respectively). Inter‐group comparison showed the mean of LVEF was significantly lower in MRI group than in 2DE group (P = 0.031), whereas there was no significant difference between 2DE group and 3DSTI group and between 3DSTI group and MRI group (P > 0.05; respectively). The EDmass and EDmassI detected by 3DSTI and MRI were (143.2 ± 40.2) g vs (190.0 ± 58.3) g and (83.2 ± 21.1) g/m(2) vs (110.1 ± 29.7) g/m(2) (P < 0.001; respectively). CONCLUSIONS: The LVEF value detected by 3DSTI is closer to that detected by MRI in DCM patients.